Effectiveness of TB cadre refreshment on increasing cadre knowledge regarding TB patient contact investigation activities - Yulanda Irma Tiara; Miranda Gracia Salsabila; M. Nur Khamid; Choiria Firdatul Ulfah (Nursing and Health Sciences Journal (NHSJ), 2025)
Indonesia ranks second globally in tuberculosis (TBC) cases after India, with Jember Regency being one of the regions in East Java with a high TBC incidence. Health cadres play a key role in TBC control through early detection, public education, and monitoring treatment adherence. A refreshment program was implemented to update cadre knowledge and strengthen their capacity. This study aims to evaluate the effectiveness of the cadre refreshment program in increasing knowledge about TBC in Jember Regency. This research employs a pre-experimental design with a one-group pretest-posttest design approach. The sample consisted of 41 health cadres selected purposively. Data were collected using questionnaires before and after the training and then analyzed using the paired t-test with a significance level 0.05. The study revealed a significant increase in cadre knowledge after participating in the training. The average pretest score was 14.9, rising to 18.9 in the posttest. The paired t-test showed a p-value of 0.001 (p < 0.05), indicating a meaningful difference in knowledge before and after the intervention. The cadre refreshment program effectively enhances cadre understanding of TBC in the Jember Regency. These findings are expected to serve as a foundation for the Health Office to optimize continuous cadre training to strengthen TBC control at the community level.